The New Left at Work: Workers’ Unity, the New Tendency, and Rank-and-File Organizing in Windsor, Ontario, in the 1970s - Antaya, Sean (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2020)
This article examines rank-and-file organizing in Windsor’s automobile factories during the 1970s. In particular, I look at the history of two organizations: Workers’ Unity and the New Tendency’s Auto Worker Group. I demonstrate how these groups were part of the North American New Left’s broader turn toward Marxism and the working class that contributed to the emergence of radical rank-and-file movements that challenged both management and bureaucratized trade union leaders. In Windsor, New Left auto workers embraced forms of autonomist Marxist politics concerned primarily with working-class self-activity at the point of production, and these activists formed connections with influential theorists and organizations in Detroit and Italy. Putting these intellectual exchanges into action, the rank-and-file organizations in Windsor used direct action in an attempt to improve working conditions and develop a radical culture of democracy on the shop floor. Although these groups were relatively short lived, their history tells us much about the trajectory of the New Left in Canada and the ways that former student activists grappled with the radical potential of 1970s working-class militancy.